Relationship of CYP3A5 genetic polymorphism and efficacy of calcium channel blockers in the treatment of Chinese end-stage renal disease patients - ZHOU Jun; CHEN Ju (Linchuang shenzangbing zazhi)
Objective To analyze the relationship between CYP3A5 genotype and antihypertensive effect of the calcium channel blockers(CCB).Methods We studied 215 maintenance hemodialysis or peritoneal hemodialysis patients from the Haikou Xiangya Hospital of Central South University.The levels of hemoglobin,serum creatinine and immunoreactive parathyroid hormone(iPTH) were determined every 3 months and blood pressure was measured simultaneously.According to the blood pressure levels,the patients were divided into the normotensive group,the controllable hypertensive group at target blood pressure and the treatment-resistant hypertensive group.The patients were classified into the nifedipine,amlodipine and felodipine groups in terms of CCB.Multiple linear regression and the Hardy-Weinberg equilibrium test were used to analyze the relationship of CYP3A5 polymorphism and efficacy of CCB via the polymeras chain reaction and bidirectional sequencing.Results The CYP3A5 genotype distributions were in Hardy-Weinberg equilibrium providing the cue from the same Mendel group.There were no significant differences in ages,gender,SBP,DBP,ASBP,ADBP,Hb and iPTH in ESRD patients with different CYP3A5 genotypes(P>0.05).There were 31 normotensive patients and 184 hypertensive patients among the 215 ESRD patients.In the normotensive group there were 14 cases of GG genotype,14 cases of 14,11 cases of GA genotype,and 6 cases of AA genotype.In the hypertensive group,there were 96 cases of GG genotype,66 cases of GA genotype,and22 cases of AA genotype.There were no significant differences in genotypes between the normotensive patients and the hypertensive patients(P = 0.702),suggesting the CYP3A5 polymorphism was not associated with the blood pressure.Multiple linear regression showed the CYP3A5 genotype was not associated with the declined blood pressure levels(P>0.05),indicating the CYP3A5 polymoiphism was not associated with antihypertensive effect of CCB.Conclusions Our study had not showed an association of CYP3A5 genotype with increased blood pressure and serum creatinine levels in ESRD patients.There was no association of CYP3A5 polymorphism with antihypertensive effect of CCB in ESRD patients.